THE CONTENT OF EDUCATIONAL AND PEDAGOGICAL FORECASTING IN UKRAINE (1917 – 1920) - Cherniak S. G. (International Journal of Innovative Technologies in Social Science, 2021)
The article is devoted to the study of the problem of the content of educational and pedagogical forecasting in Ukraine in the period 1917 – 1920. The author concludes that the content of educational and pedagogical forecasting in Ukraine in the period 1917-1920 is manifested in the development of its national paradigm, the search for variable systems and models, technologies and methods of training teachers. The problem of educational and pedagogical forecasting within certain limits is a component and objectively existing, independent, defining direction, which allows to study the holistic process of development of preschool, secondary and higher education in Ukraine, its features, color; identify the leading trends, ideas, creative experience of training, which determines the positive transformation of the values of Ukrainian society; to outline ways to update educational and pedagogical forecasting in modern socio-political and economic conditions and to update the accumulated material from the past in the realities of pedagogical theory and practice of today.